2002
DOI: 10.1002/jat.848
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the predictive validity of Frog Embryo Teratogenesis Assay—Xenopus (FETAX)

Abstract: Frog Embryo Teratogenesis Assay-Xenopus (FETAX) is a 4-day, alternative developmental toxicity assay designed to pre-screen chemicals and environmental mixtures. An approach used in the scoring of FETAX results, which focuses on the determination of characteristic abnormalities induced by a given test material, was used to evaluate results from previous validation efforts. Characteristic abnormalities are induced specifically by exposure to a given test material and are determined by the relationship between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…In the present paper, we employed a modified frog embryo teratogenesis assay Xenopus (FETAX) protocol (Fort and Paul, 2002; Yu et al, 2011) to assess UVI3003-induced malformations in X. tropicalis embryos specific to certain developmental windows of chemical exposure. In a previous study, we found that the well-known agonist of RXR, triphenyltin (TPT), induced stage-specific malformations and phenotypic changes in Xenopus embryos (Yuan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present paper, we employed a modified frog embryo teratogenesis assay Xenopus (FETAX) protocol (Fort and Paul, 2002; Yu et al, 2011) to assess UVI3003-induced malformations in X. tropicalis embryos specific to certain developmental windows of chemical exposure. In a previous study, we found that the well-known agonist of RXR, triphenyltin (TPT), induced stage-specific malformations and phenotypic changes in Xenopus embryos (Yuan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Breeding was induced by subcutaneous injection of human chorionic gonadotrophin (hCG) (Zhejiang, China) as described (Yu et al, 2011; Hu et al, 2015a). The exposure experiments were conducted following the Frog Embryo Teratogenesis Assay (FETAX) protocol (Fort and Paul, 2002) with some modifications. Briefly, approximately 12 h after the second injection of hCG, adults were removed from their tanks, and embryos were harvested without removing the jelly coats (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Possible explanations include: non-anthropogenic differences in water quality, maternal transfer of pollutants, distinct genetic groups and epigenetic effects caused by early exposure to pollutants from the ambient aquatic environment. Although conductivity and DO values differed between sites, it has been reported that values of 42-1,790 lS/cm have no effect in FETAX (Fort and Paul 2002), and it seems unlikely that the differences in DO would affect these endpoints. It has also been reported that different races of Rana temporaria display different age and size at metamorphosis in the laboratory, depending on latitude of the parent frogspawn (Laugen et al 2003), although the range of sampling sites in the latter study was 14°N (*1,500 km) compared to 1°N latitude (*160 km) here.…”
Section: Growth and Developmentmentioning
confidence: 91%
“…However, because of economic and ethical constrains with in vivo studies, alternatives for in vivo toxicity studies are being developed and validated , Fort et al 2002, Spielmann et al 2006. Due to the complexity of the developmental process, it is a challenge to develop non-animal based methods that cover the whole developmental process .…”
Section: Developmental Toxicity Of Nanoparticlesmentioning
confidence: 99%
“…To assess possible adverse eff ects of NPs on the developing fetus, in vivo developmental toxicity studies can be performed in for example rats or mice. However, because of economic and ethical constrains with in vivo studies, alternatives for in vivo toxicity studies are being developed and validated , Fort and Paul 2002, Spielmann et al 2006). …”
Section: Introductionmentioning
confidence: 99%